Seizures caused by brain tumors in children. (January 2017) - Sánchez Fernández, Iván; Loddenkemper, Tobias
Highlights: Pediatric brain tumors are the most common cause of death in pediatric cancer. Seizures are one of the most common symptoms in pediatric brain tumors. Supratentorial brain tumors that involve gray matter are more epileptogenic. Dysembryoplastic neuroepithelial tumor and ganglioglioma are particularly epileptogenic. Newer drugs with less interactions are preferred for seizures caused by tumors. Abstract: Purpose: To review the epidemiology, clinical features, and treatment of seizures secondary to pediatric brain tumors. Method: Literature review. Results: Pediatric brain tumors are the most common solid pediatric tumor and the most common cause of death in pediatric cancer. Seizures are one of the most common symptoms of pediatric brain tumors. Factors associated with increased risk of seizures include supratentorial location, gray matter involvement, low-grade, and certain histological features—especially dysembryoplastic neuroepithelial tumor, ganglioglioma, and oligodendroglioma. Leukemic infiltration of the brain, brain metastases of solid tumors, and brain injury secondary to chemotherapy or radiotherapy can also cause seizures. Mechanisms by which brain tumors cause seizures include metabolic, and neurotransmitter changes in peritumoral brain, morphologic changes – including malformation of cortical development – in peritumoral brain, and presence of peritumoral blood products, gliosis, and necrosis. As there is a high degree of uncertainty on how effective different antiepileptic drugs are for seizures caused by brain tumors, choices are often driven by the interaction and side effect profile. Classic antiepileptic drugs – phenobarbital, phenytoin, or carbamazepine – should be avoided as they may alter the metabolism of chemotherapeutic agents. Newer drugs – valproate, lamotrigine, topiramate, zonisamide, and levetiracetam – may be the preferred option in patients with tumors because of their very limited interaction with chemotherapy. Conclusion: Seizures are a common presentation of pediatric brain tumors, especially in supratentorial tumors with gray matter involvement. Antiepileptic drug therapy is usually driven by the interaction and side effect profile and newer drugs with few interactions are generally preferred.